Implementation Of A Multi-Airport System For Airports In The New Capital City Of Indonesia - Adi Nugroho; Bayu Arsan; Zannah Astaria Dhika (Eduvest - Journal of Universal Studies, 2022)
The development plan for the Capital City of Indonesia on Kalimantan Island requires support from various aspects, such as the economy, government, and transportation. Recognizing the potential for economic and trade development accompanied by the heavy traffic in the IKN area, it needs to be in line with adequate accessibility. The existing airports on Kalimantan Island, especially in East Kalimantan, have the potential to meet the demands of the community in the future. This paper aims to analyze the possibility of existing airports around the new Capital City of Indonesia (IKN) area to be used as a Multi-Airports System to support the successful transfer of Capital City of Indonesia.